Silent networks: The role of inaccurate beliefs in reducing useful social interactions - Ronak Jain; Vatsal Khandelwal (University of Zurich, Department of Economics, 2024)
Inaccurate beliefs about social norms can reduce useful social interactions and adversely affect an individual's ability to deal with negative shocks. We implement a randomized controlled trial with low-income workers in urban India who lack access to formal financial and healthcare support. We find that the majority of individuals underestimate their community's willingness to engage in dialogue around financial and mental health concerns. Belief correction leads to a large increase in the demand for network-based assistance. We show that the effects are driven by a reduction in the perceived costs of violating social norms arising due to concerns around reputation and insensitivity. We structurally estimate a network diffusion model and predict that our belief correction intervention will not lead to a shift in equilibrium engagement. Consistent with this, 2 years later, we find that the average beliefs of those exposed to the intervention are significantly more optimistic but still lower than the information delivered in the experiment. We compute the strength of counterfactual interventions needed to generate a sustained effect and find that belief correction can be used to generate both the demand and funding for such policies.
Keywords: C93; D83; D91; I12; I31; Z13; 330; Social Networks; Social Norms; Beliefs; Risk Sharing; Mental Health